Designing English Learning Materials Based on Hots Integrated Hypertext at Senior High School Level - Munawaroh, Tatu; Ruhiat, Yayat; Juniardi, Yudi; Gumelar, Rizdki Elang (PT FORMOSA CENDEKIA GLOBAL, 2024)
Teaching materials is a set of teachers learning guidelines to make learning more effective. Through hypertext as a learning medium and Hots as a thinking method that directs students to be critical in thinking, teaching materials based on Hots integrated with hypertext can be applied to class X at the high school level. The purpose of this study was to develop English teaching materials. The research method used was the ADDIE model with a qualitative research type. Through three experts, namely material experts, learning design experts, and media experts, the results of the study showed that based on the results of a limited trial of 35 students at SMAN 10 Pandeglang showed an average value of 95.29%, while a broad trial of 105 students from the three schools produced an average value of 95.76%, which indicates that the acceptance of teaching materials is very good. So, in other words this teaching material is able to create a conducive learning atmosphere.